Kinematics of Polygonal Fault Systems: Observations from the Northern North Sea - Wrona, Thilo; Magee, Craig; Jackson, Christopher A-L.; Huuse, Mads; Taylor, Kevin G. (Frontiers in Earth Science, 2017)
Layer-bound, low-displacement normal faults, arranged into a broadly polygonal pattern, are common in many sedimentary basins. Despite having constrained their gross geometry, we have a relatively poor understanding of the processes controlling the nucleation and growth (i.e. the kinematics) of polygonal fault systems. In this study we use high-resolution 3-D seismic reflection and borehole data from the northern North Sea to undertake a detailed kinematic analysis of faults forming part of a seismically well-imaged polygonal fault system hosted within the up to 1000 m thick, Early Palaeocene-to-Middle Miocene mudstones of the Hordaland Group. Growth strata and displacement-depth profiles indicate faulting commenced during the Eocene to early Oligocene, with reactivation possibly occurring in the late Oligocene to middle Miocene. Mapping the position of displacement maxima on 137 polygonal faults suggests that the majority (64%) nucleated in the lower 500 m of the Hordaland Group. The uniform distribution of polygonal fault strikes in the area indicates that nucleation and growth were not driven by gravity or far-field tectonic extension as has previously been suggested. Instead, fault growth was likely facilitated by low coefficients of residual friction on existing slip surfaces, and probably involved significant layer-parallel contraction (strains of 0.01-0.19) of the host strata. To summarize, our kinematic analysis provides new insights into the spatial and temporal evolution of polygonal fault systems.